Brassinosteroid's multi-modular interaction with the general stress network customizes stimulus-specific responses in Arabidopsis. (September 2016) - Bjornson, Marta; Dandekar, Abhaya M.; Chory, Joanne; Dehesh, Katayoon
Graphical abstract: Highlights: Brassinosteroids (BR) modulate the general stress response (GSR). Exogenously applied BR reduces flg22-, but enhances wound-induced GSR. Wound-activated GSR in BR-treated plants heightens resistance to Botrytis cinerea . Point of BR-GSR interaction is downstream of membrane receptor circuitry. Multiple interaction points between BRs and stress signaling tailor plant responses. Abstract: Adaptation to fluctuating environmental conditions is a universal feature of plant life, governed by fundamental mechanisms optimizing resource allocation. This balance is achieved in part through tightly regulated communication networks among growth and stress response signaling pathways. Understanding the communication modules between brassinosteroids (BRs), the ubiquitous hormones known to control growth and stress adaptation, and the general stress response (GSR), a rapid and transient transcriptional output in response to perturbations, provides an optimal platform to unravel new facet(s) of plant stress adaptation. Here, we explore communication facets of BR with GSR via in planta quantification of the GSR in Arabidopsis expressing luciferase driven by a functional GSR cis-element, the Rapid Stress Response Element (4xRSRE:LUC). We establish that application of exogenous BR suppresses microbe-associated molecular pattern-activated GSR, but enhances the wound-triggered GSR. The enhanced wound-activated GSR in BR-treated plants results in a greater wound-induced resistance to Botrytis cinerea . A combination of molecular genetics using BR signaling mutants and application of an activator of BR signaling, bikinin, confirms these results and places the chief point of BR-GSR interaction downstream of potential membrane receptor circuitry. These results support a multi-modular interaction between BRs and stress signaling, instrumental in customizing stimulus-specific responses in Arabidopsis.